Inside Himalaya - Photographs by Pao, Basil; Foreword by Palin, Michael (London Weidenfeld & Nicolson, 2004)
This is a photographic record of Michael Palin's journey through the countries bordering the Himalayan mountains, accompanying the BBC television series 'HIMALAYA'.
Include Color Illustrations.
The History of Britain's Most Famous World War II Fighter.
Keywords: Travel -- Himalaya Mountains Region -- Palin, Michael -- South Asia